Extraction Of Fish Gelatin From Surimi Processing By-Products Aided By Enzymes Using Response Surface Methodology - Kee, Huey Ying (2013)
Gelatin was extracted from surimi processing by-product of ribbon fish (Trichiurus lepturus) specie that consisted of skins, bones and scales, aided by enzymes, bromelain and papain. The extraction process was optimized using response surface methodology (RSM) approach with a 4-factor and 5-level central composite rotatable design (CCRD). The effects of enzyme concentration (X1), acid pretreatment time (X2), extraction temperature (X3) and extraction time (X4) on responses, gelatin yield (Y1) and gel strength (Y2) were investigated. Optimum conditions obtained for gelatin extraction aided by bromelain (EFGB) were: enzyme concentration, 0.03%; acid pretreatment time, 1.5 hr; extraction temperature, 41 ºC and extraction time, 5 hr whilst that for extraction aided by papain (EFGP) were: enzyme concentration, 0.03%; acid pretreatment time, 4 hr; extraction temperature, 42 ºC and extraction time, 5.1 hr. The predicted values for response gelatin yield and gel strength of EFGB were 19.2% and 73.6 g while the actual experimental values obtained were 18.3% and 62.9 g. The predicted values for response gelatin yield and gel strength of EFGP were 18.7% and 37.0 g while the actual experimental values obtained were 18.5% and 34.6 g. The gelatin yield of both EFGB and EFGP were increased by about 50% compared to the gelatin yield for gelatin extracted without enzyme (EFG). However the gel strength for both EFGB and EFGP were reduced compared to that of EFG, which was 76.0 g.